A MANAGEMENT ANALYSIS OF DENGUE HEMORRHAGIC FEVER (DHF) CONTROL AT ROWOREJO PUBLIC HEALTH CENTER, NEGERI KATON SUBDISTRICT, PESAWARAN REGENCY, 2025 - Sari, Yunita; Aryawati, Wayan; Muhani, Nova (HEARTY, 2026)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus, transmitted through the Aedes mosquito vector, which breeds in water containers that collect rainwater. The rainy season is the period when DHF cases occur most frequently. In Pesawaran Regency, the prevalence of DHF declined in 2023 compared to the previous year, with 149 cases reported in 2023, down from 432 cases in 2022. However, data from the Pesawaran District Health Office in 2024 indicated an increase to 252 DHF cases. This rising trend warrants serious attention to understand the contributing factors behind the increase in DHF cases in Pesawaran. This study aims to analyze the management of DHF control at the Roworejo Public Health Center in Pesawaran Regency. This is a qualitative study involving six informants, using in-depth interviews as the primary data collection method. The findings reveal that DHF control planning at the Roworejo Public Health Center has been systematically designed in accordance with existing guidelines, covering aspects such as budgeting, methods, facilities, and community participation. However, shortcomings remain in the provision of incentives for health cadres and the maintenance of facilities. The organizational structure operates based on a task-based and function-oriented (tupoksi) approach. All DHF control measures, including fogging, vector control (PSN), health education, and epidemiological investigations, have been implemented in accordance with Standard Operating Procedures. Supervision of DHF control efforts is considered adequate from both management and field implementation perspectives.